Characteristics of fermented goat milk using combination of kombucha and Lactobacillus casei starters. (November 2019) - Nurliyani,; Indratiningsih,; Widodo,; Sukarno, A S; Suciati, F
Abstract: Kombucha is potential for starter for milk fermentation process. This study was aimed to evaluate the effect of combination of L. casei and kombucha starters on quality of fermented goat milk. In this study, control group (T0) used 5% L. casei ; T1 and T2 groups used 2% L. casei combined with 5% and 10% kombucha, respectively. Data of microbiological (total of bacteria, probiotics, yeast, and acetic acid bacteria); chemical (pH, acidity, lactose, fat, protein, moisture, and fatty acid); antioxidant activity, viscosity, and sensory qualities were analysed using one-way ANOVA. The results showed that the addition 5 and 10% of kombucha starter did not affect the total of bacteria and probiotic, but significantly affected (P<0.01) the total yeast and total acetic acid bacteria. Acidity, pH, lactose, fat, and protein were similar, whereas the linoleic acid was higher in T1 than T2 and T0. Moisture content and antioxidant activity of T2 were higher than T0 and T1. The viscosity of T1 and T2 were lower (P<0.05). Sensory acceptance of fermented milk of T0 and T1 were higher than T2. It is concluded that L. casei combined with 5% kombucha starters (T1) was the best proportion to ferment goat milk.